Завьялово: помню всех поименно - Миронова Римма Тимофеевна (Удмуртия, 2014)
Экземпляры: ЦБ (20160224) / Инвентарный номер: 51798 / Цена: 200.00 / Сис.шифр: 63.3(2Рос.Удм) / Авт.знак: М 64 / ГРНТИ: 03.23 / ББК: 63.3(2Рос.Удм)